2012
DOI: 10.1186/1746-6148-8-119
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of the ovary and small follicle pool from mid fetal life to pre-puberty in the African elephant (Loxodonta africana)

Abstract: BackgroundFollicle numbers and developing ovarian morphology, particularly with reference to the presence of interstitial tissue, are intimately linked within the ovary of the African elephant during the period spanning mid-gestation to puberty. These have not been previously quantified in any studies. The collection of 7 sets of elephant fetal ovaries between 11.2 and 20.2 months of gestation, and 29 pairs of prepubertal calf ovaries between 2 months and 9 years of age during routine management off-takes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
6
3
0
Order By: Relevance
“…The follicle reserve of the Asian elephant in this study was found to consist of early primary follicles (a single layer of cuboidal granulosa cells), true primary follicles (all cuboidal granulosa cells), and true primordial follicles (a single layer of squamous granulosa cells) grouped together as small follicles within the ovary. This is in agreement with previous studies on the African elephant, where the type of small follicles mostly found were early primary follicles and true primary follicles rather than primordial follicles ( Stansfield, Nöthling & Allen, 2012 ; Stansfield, Nothling & Ansari, 2011a ). Furthermore, the oocytes are larger in true primary follicles than in early primary follicles, suggesting activation of the follicle ( Picton, 2001 ) and also that true primary follicles do not belong to the ovarian reserve of the small follicle pool in the African elephant ( Stansfield, Nöthling & Allen, 2012 ) and possibly the Asian elephant as well.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The follicle reserve of the Asian elephant in this study was found to consist of early primary follicles (a single layer of cuboidal granulosa cells), true primary follicles (all cuboidal granulosa cells), and true primordial follicles (a single layer of squamous granulosa cells) grouped together as small follicles within the ovary. This is in agreement with previous studies on the African elephant, where the type of small follicles mostly found were early primary follicles and true primary follicles rather than primordial follicles ( Stansfield, Nöthling & Allen, 2012 ; Stansfield, Nothling & Ansari, 2011a ). Furthermore, the oocytes are larger in true primary follicles than in early primary follicles, suggesting activation of the follicle ( Picton, 2001 ) and also that true primary follicles do not belong to the ovarian reserve of the small follicle pool in the African elephant ( Stansfield, Nöthling & Allen, 2012 ) and possibly the Asian elephant as well.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies on the African elephant, where the type of small follicles mostly found were early primary follicles and true primary follicles rather than primordial follicles ( Stansfield, Nöthling & Allen, 2012 ; Stansfield, Nothling & Ansari, 2011a ). Furthermore, the oocytes are larger in true primary follicles than in early primary follicles, suggesting activation of the follicle ( Picton, 2001 ) and also that true primary follicles do not belong to the ovarian reserve of the small follicle pool in the African elephant ( Stansfield, Nöthling & Allen, 2012 ) and possibly the Asian elephant as well. It is necessary to determine the number of small follicles, including primordial, early primary and true primary follicles, in the ovaries of elephants, as the follicle reserve supplies oocytes throughout the reproductive cycle ( Stansfield, Nothling & Ansari, 2011a ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In mouse ovaries, due to a large number of reproductive follicles that rupture at birth, the limited remaining germ cells are eventually wrapped in primitive granulosa cells and to form the primordial follicle pool [11,12]. As we known, the traditional view may suggest that the ovarian function gradually decrease with the female ages.…”
Section: Introductionmentioning
confidence: 99%